Country-Level Performance of New Experience Products in a Global Rollout: The Moderating Effects of Economic Wealth and National Culture. Issue 4 (December 2014) - Griffith, David A.; Yalcinkaya, Goksel; Rubera, Gaia
International marketing manager decisions pertaining to a new experience product's global rollout are critical to the product's country-level performance. Extending work on the lead–lag and success-breeds-success effects, the authors examine how the country-specific factors of economic wealth and national culture influence the effects of a new experience product's global rollout decisions (i.e., the time lag from initial lead country introduction to target country introduction and the number of countries in which the product was introduced before its introduction in the target country) on the product's country-level performance. The authors employ hierarchical linear modeling and, from an examination of 259 unique movies gathered from 16 countries, corresponding to 2, 523 total entries between 2006 and 2007, find significant interaction effects between a country's economic wealth and national culture and time lag and target country position on the new experience product's country-level performance. The authors conclude with a discussion of the theoretical and practical implications.